SCALE EFFECT IN SEISMOTECTONICS - G. G. Kocharyan (Геодинамика и тектонофизика)
This publication consolidates and analyses experimental data in a wide range of scales in seismotectonics and geomechanics, from a micro-size seismic event (an earthquake focus of a few centimetres) to a mega earthquake. It reviews regularities in changes of geometric parameters of faults and fractures in various ranks, their mechanical properties, linear sizes of earthquake foci, time of preparation of dynamic events, and seismic energy.Averaging through the whole range of scales yields ratios close to the law of geometrical similarity. A more detailed consideration gives grounds to conclude that several hierarchic levels can be distinguished and, in different scale, changes of parameters of events follow laws that differ and often deviate from the laws of similarity.It is shown that linear sizes, L from ~500 to 1000 m comprise a transitional range that is a border between two ranges characterized by significantly different scale ratios. Seismicity with shallow foci which is associated with mining operations should be noted separately.According to energy calculation with reference to categories of seismic events, it is established that earthquakes of the Baikal rift system show an anomalous trend of strongly increasing specific energy with increasing scales. In the range of moment magnitudes from 5 to 6.3, an average specific value of seismic energy is higher than an average global value for the same range at least by a factor of 25. It should be clarified whether such an effect is an artefact related to errors in seismic energy calculations or an actual physical effect that is still unexplained.